Coherence of character and temperament drives personality change toward well being in person-centered therapy. Issue 1 (20th January 2023) - Garcia, Danilo; Cloninger, Kevin M.; Cloninger, C. Robert
Abstract : Purpose of review: People and communities around the world face many crises, including increasing burdens from disease, psychopathology, burn-out, social distrust, and acts of hate and terrorism. Personality disorder is arguably both a root cause and a consequence of these problems, creating a vicious cycle of suffering caused by fears, immoderate desires, and social distrust that are inconsistent with rational goals and prosocial values. Fortunately, recent advances in understanding the biopsychosocial basis and dynamics of development in personality and its disorders offer insights to address these problems in effective person-centered ways. Recent findings: Fundamental advances have been made recently in the understanding of the psychobiology and sociology of personality in relationship to health, and in basic mechanisms of personality change as a complex process of learning and memory. Promotion of self-awareness and intentional self-control releases a strong tendency for people to seek coherence of their emotions and habits with what gives their life meaning and value. Summary: People have a strong drive to cultivate personalities in which their emotions and habits are reliably in accord with reasonable goals and prosocial values. Person-centered therapeutics provide practical ways to promote a virtuous cycle of increasing well being for individuals and their communities and habitats.